Prevalence and etiology of dental trauma in schoolchildren aged 6 to 12 years - Ana de Lourdes Sá de Lira; Luís Paulo da Silva Dias; Cassius Wander Coelho Martins; Tito Cacau Sousa Santos (Brazilian Journal of Oral Sciences, 2018)
Aim: To investigate the prevalence and etiological factors of dental trauma in school-age children aged 6 to 12 years. Methods: A study was developed in children and adolescents between the ages of 6 and 12 of both genders enrolled in 3 municipal public schools. An oral examination of the permanent or deciduous incisors was performed, if they were still present in the oral cavity, to evaluate the presence of dental trauma, need for treatment and sequels, and the method of examination and classification of dental trauma of O'Brien. Results: The prevalence of dental trauma was 4.03% (n=29). The most verified traumas were enamel crack / enamel fracture and enamel / dentin fracture without pulp exposure. It was observed that the most affected teeth were the permanent upper central incisors and the age at which trauma was most observed was 11 years, the main etiological factor was fall from a height, in 65.3% of schoolchildren (n=19). Conclusion: The prevalence of dental trauma was 4.03%, with no statistically significant difference between genders. The permanent right upper central incisor was the most affected, occurring predominantly at home and at school. The dissemination of information about dental trauma and emergency protocols to parents and teachers need to be encouraged.